ANALISIS DAYA TAHAN DENGAN STAMINA TERHADAP SALAH SATU ATLET SEPAK BOLA TARKAM - Aggil Ahmad Ramadhan; Raden Akhmad Aqtoo; Amrul Hayat; Qoyyum Saputra; Hikmal Soulisa; Tubagus Lucky Tri Iman Setiawan; Siti Nur Azizah; Nuri Maulida; Fauzan Amrullah Ramadhan; Muhammad Faiza Akhira Ramadhan (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the endurance and stamina on the performance of a specific football athlete tarkam. Modern football demands peak physical condition, where endurance and stamina are key success factors. Endurance enables athletes to maintain game intensity for a full 90 minutes and recover quickly, while stamina supports repetitive sprints and physical duels. The research method employed is a qualitative case study approach, involving interviews, and data analysis from the selected football athlete. The findings indicate that high levels of endurance and stamina positively correlate with improved athlete performance, including passing accuracy, running speed, and decision-making ability under pressure. Conversely, fatigue resulting from low endurance and stamina negatively impacts game quality. The implications of this research highlight the importance of integrated training programs to enhance endurance and stamina for optimizing football athlete performance